An opportunity to reduce the burdens and inequalities in cardiovascular disease and gastric cancer caused by dietary salt: IMPACTNCD microsimulation study. (13th November 2015) - Kypridemos, Chris; Guzman-Castillo, Maria; Hyseni, Lirije; Bandosz, Piotr; Allen, Kirk; Buchan, Iain; Capewell, Simon; O'Flaherty, Martin
Abstract: Background: Dietary salt intake determines a substantial proportion of cardiovascular disease and gastric cancer. Since 2005, the UK has implemented a series of policies to reduce dietary salt, and salt consumption has declined by 10%. We compared the effect of two strategies on future disease burdens and inequalities in cardiovascular disease and gastric cancer in England. Methods: We used the validated IMPACTNCD model (discrete time, dynamic, stochastic microsimulation) to predict disease burdens between 2020 and 2035. Two scenarios were considered. The first was present policy, with the assumption that the recent observed downward logarithmic trend in salt consumption continues. The second was adding mandatory reformulation, with the assumption that reformulation of processed foods achieves a steeper, linear salt decline, reaching the national target (6 g/day) by 2020 and levelling out. Both scenarios assume a 5 year time lag for cardiovascular disease (10 year lag for gastric cancer) and no risk for salt consumption of less than 3 g/day. Salt consumption was modelled after measurements of 24 h urinary sodium excretion. Only effect on primary prevention was considered. We stratified the English population into fifths by the Index of Multiple Deprivation. Uncertainty intervals (UI) were estimated by second order Monte Carlo simulation and represent the probabilistic sensitivity analysis. Findings: For the present policy we estimated about 2 100 000 cases of cardiovascular disease (95% UI 1 900 000–2 300 000) and 530 000 deaths (500 000–560 000) between 2020 and 2035, 78 000 cases of gastric cancer (70 000–85 000), and 43 000 deaths from gastric cancer (38 000–47 000). The addition of mandatory reformulation might prevent or postpone about 66 000 cases of cardiovascular disease (55 000–77 000), and lead to 6800 fewer deaths (4800–8700), while also preventing about 4700 cases of gastric cancer (4200–5300) and 2100 deaths (1800–2400). Mandatory reformulation could also achieve a larger relative reduction in burden of these conditions among the most deprived quintile (–3·5%, 95% UI −4·0 to −2·9) than in the least deprived quintile (–3·1, −3·6 to −2·6). Both inequality and disease burden reduction were greater for men than for women. Interpretation: Existing salt reduction policies are effective. These results suggest, however, that failure to implement mandatory reformulation represents an opportunity cost that will generate avoidable disease; and an opportunity to reduce socioeconomic and gender inequalities in health will be lost. Funding: Medical Research Council Health eResearch Centre, grant MR/K006665/1 (IB, CK); National Institute for Health Research (PB, MG-C); British Heart Foundation (PB, MG-C); and Higher Education Funding Council for England (SC, MO'F).